Integrative Performance Analysis of a Novel Bone Level Tapered Implant. (March 2016) - Dard, M.; Kuehne, S.; Obrecht, M.; Grandin, M.; Helfenstein, J.; Pippenger, B.E.
Primary mechanical stability, as measured by maximum insertion torque and resonance frequency analysis, is generally considered to be positively associated with successful secondary stability and implant success. Primary implant stability can be affected by several factors, including the quality and quantity of available bone, the implant design, and the surgical procedure. The use of a tapered implant design, for instance, has been shown to result in good primary stability even in clinical scenarios where primary stability is otherwise difficult to achieve with traditional cylindrical implants—for example, in soft bone and for immediate placement in extraction sockets. In this study, bone-type specific drill procedures are presented for a novel Straumann bone level tapered implant that ensure maximum insertion torque values are kept within the range of 15 to 80 Ncm. The drill procedures are tested in vitro using polyurethane foam blocks of variable density, ex vivo on explanted porcine ribs (bone type 3), and finally in vivo on porcine mandibles (bone type 1). In each test site, adapted drill procedures are found to achieve a good primary stability. These results are further translated into a finite element analysis model capable of predicting primary stability of tapered implants. In conclusion, we have assessed the biomechanical behavior of a novel taper-walled implant in combination with a bone-type specific drill procedure in both synthetic and natural bone of various types, and we have developed an in silico model for predicting primary stability upon implantation.